Glochidion liangkwangense (Phyllanthaceae), a new species from Guangdong and Guangxi Provinces, China - Yao, Gang; Luo, Shixiao; Huang, Jiuxiang; Song, Zhuqiu (Phytotaxa, 2024)
Glochidion liangkwangense, a new species from Guangdong and Guangxi Provinces, China, belonging to subgenus Pseudoactephila, is here described. The new species grows in limestone hills. It is most similar to Glochidion anthopotamicum in morphology, but it could be easily distinguished from the later by its sepals that are erect and usually extend outward (vs. spreaded or even reflexed at the upper part, and jointly formed a urceolate shape at the lower part), sepals of female flowers in 2 series that are different in shape and size (vs. in 2 series but subequal in both of shape and size), disc segments in flowers that are short and spatulate to slightly T-shaped (vs. long and linear), and capsules that are triangular-globose (vs. globose) in shape. Additionally, the new species is considered here as Least Concern (LC) in conservation status. Key to all species of the subgenus Phyllanthodendron in Glochidion is provided.